A Stylistic Analysis Of Selected Graded Readers And Chinese Second Language Learners’ Aesthetic Response Towards Selected Stylistic Devices - June, Chiang Kai Sing (2019)
Mostly used in extensive reading programmes, graded readers (GRs), which come under the umbrella of language learner literature (LLL), are weighted with the obligation to engage second language (L2) learners. Many publishers of GRs focus on strong plots using reduced language code to achieve this objective; however, there are stakeholders who recognise the importance of retaining good natural literary discourse. Rosenblatt's transactional reader response theory and Miall and Kuiken's foregrounding theory support the notion that stylistic devices have the capacity to create evocation in the reader which could heighten the aesthetic or pleasurable reading experience. Taking this into consideration, the study examined the effect of literariness in GRs for them to be considered good by investigating the extent of employment of selected stylistic devices in GRs that are considered good (awardwinning GRs) and that are considered less good (non-award winning GRs) to determine the importance of literariness in making successful GRs. The study also compared Chinese L2 learners’ aesthetic response towards texts without and with selected stylistic devices . As such, the study was a two-phased investigation. To examine the GRs (phase one), a stylistic analysis was carried out to compare the occurrence of figures of speech, the selected style markers, in three award and six corresponding non-award winning texts.